Notch signaling in cancers: mechanism and potential therapy - Chen, Chen; Du, Yan; Nie, Rongzu; Wang, Shuangshuang; Wang, Hang; Li, Peifeng (Frontiers in Cell and Developmental Biology, 2025)
The Notch signaling pathway is an evolutionarily conserved intercellular signaling cascade that regulates a number of cellular processes, including cell development, proliferation, apoptosis, and genome stability. The Notch signaling pathway is pervasive in the human body, affecting tumorigenesis and progression, which is one of the most significant signaling pathways in this regard, influencing various receptors and cellular functions of tumor cells. Aberrant expression or mutation of Notch has been linked to the onset and progression of a variety of malignant tumors. In this review, we discussed the mechanism of Notch signaling in lung, liver and colorectal cancer and explored future strategies and directions for cancer treatment by modifying the Notch signaling pathway.